The value of point-of-care CD4+ and laboratory viral load in tailoring antiretroviral therapy monitoring strategies to resource limitations. (24th September 2017) - Hyle, Emily P.; Jani, Ilesh V.; Rosettie, Katherine L.; Wood, Robin; Osher, Benjamin; Resch, Stephen; Pei, Pamela P.; Maggiore, Paolo; Freedberg, Kenneth A.; Peter, Trevor; Parker, Robert A.; Walensky, Rochelle P.
Abstract : Objective: To examine the clinical and economic value of point-of-care CD4 + (POC-CD4 + ) or viral load monitoring compared with current practices in Mozambique, a country representative of the diverse resource limitations encountered by HIV treatment programs in sub-Saharan Africa. Design/methods: We use the Cost-Effectiveness of Preventing AIDS Complications-International model to examine the clinical impact, cost (2014 US), and incremental cost-effectiveness ratio [/year of life saved (YLS)] of ART monitoring strategies in Mozambique. We compare: monitoring for clinical disease progression [clinical ART monitoring strategy (CLIN)] vs. annual POC-CD4 + in rural settings without laboratory services and biannual laboratory CD4 + (LAB-CD4 + ), biannual POC-CD4 +, and annual viral load in urban settings with laboratory services. We examine the impact of a range of values in sensitivity analyses, using Mozambique's 2014 per capita gross domestic product (620) as a benchmark cost-effectiveness threshold. Results: In rural settings, annual POC-CD4 + compared to CLIN improves life expectancy by 2.8 years, reduces time on failed ART by 0.6 years, and yields an incremental cost-effectiveness ratio of 480/YLS. In urban settings, biannual POC-CD4 + is more expensive and less effective than viral load. Compared to biannual LAB-CD4 +, viral load improves life expectancy by 0.6 years, reduces time on failed ART by 1.0 year, and is cost-effective (440/YLS). Conclusion: In rural settings, annual POC-CD4 + improves clinical outcomes and is cost-effective compared to CLIN. In urban settings, viral load has the greatest clinical benefit and is cost-effective compared to biannual POC-CD4 + or LAB-CD4 + . Tailoring ART monitoring strategies to specific settings with different available resources can improve clinical outcomes while remaining economically efficient. Abstract : Supplemental Digital Content is available in the text